Complications and Management of Penile Girth Enhancement with Acellular Dermal Matrix. Issue 12 (24th October 2019) - Xu, Tingmin; Zhang, Guoxi; Bai, Wenjun; Li, Qing; Yang, Anpu; Lin, Qiushi; Xu, Tao; Zhang, Xiaowei
Abstract: Introduction: Acellular dermal matrix (ADM) is a common filler used widely in clinical practice to increase penile girth for cosmetic reasons, but there are few studies on its complications. Aim: The aim of this study was to investigate and analyze the complications of penile girth enhancement (PGE) with ADM. Methods: The medical records of 78 patients who underwent PGE with ADM between June 2016 and January 2019 were retrospectively reviewed. Main Outcome Measure: Related complications and their subsequent management were summarized and analyzed. Results: 78 patients (mean age 31.14 years [21−66 years]) received PGE with ADM. At the 3-month follow-up, the penile circumference was increased by 1.1 (0.5−2.1) cm on average. There were 47 patients with erectile discomfort, 12 with delayed healing, 10 with unobvious augmentation effect, 8 with wound hematoma, 7 with prepuce edema, 4 with wound infection, and 3 patients with skin necrosis of the dorsal side. 7 patients eventually underwent ADM removal. Clinical Implications: These adverse complications indicate that ADM should be used with caution for PGE. Strength & Limitations: This study adds important data, as there are few published reports on the complications of PGE with ADM. However, this study did not compare postoperative complications with ADM to those seen with other filler material. Conclusion: Even with standardized surgical methods and rigorous postoperative care, complications of PGE using ADM are severe, which indicates that it is not an ideal or safe method for PGE.